Occurrence of paracrystalloids and their particles in resistant and susceptible carnation plants infected with Fusarium oxysporum f.sp. dianthi race 2 - B. Ouellette, Guillemond; Rioux, Danny; Simard, Marie; P. Baayen, Robert (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2004)
AbstractUncommon, opaque particles (of approximately 20-22 nm, referred to as OP), aggregating into paracrystalloids occurred only next to colonized cells in carnation plants of either a susceptible or resistant cultivar (cv.) infected with Fusarium oxysporum f.sp. dianthi. In the susceptible plant, those structures occurred in vessel lumina and host walls, apparently associated with their alterations, but not in parenchyma cells, a situation which was the exact opposite of that observed in resistant plants. In comparison with apparently similar structures reported in other systems, paracrystalloids and their OPs did not seem to have exact counterparts in plants infected with viruses or fungi, although similar paracrystalloids were observed in nematode-infected plants. The OPs were associated in both cvs. with fine opaque matter, often displaying fine filamentous structures, and were in addition connected to fungal cells in the susceptible cv. Similar structures also extended through host walls into adjoining cells; these relations with parenchyma cells in resistant plants were interpreted as if the particles therein were akin to, if not exactly of the same nature as those in susceptible plants. As the opaque matter, the filamentous structures and the OPs were interrelated and associated with pathogen cells, it seemed warranted to assume that the OPs were issued from the pathogen.